Physical science - Jerry Schad (Brooks/Cole Pub. Co., 1996)
Schad successfully leads students on an exploration of key physical concepts and their applications in the four disciplines of physical science. By repeatedly linking the fundamental discoveries and ideas of physics and their applications in other fields, the author helps students see the underlying simplicity and unity of nature, and presents a balanced coverage of topics. Schad writes conceptually and descriptively, introducing mathematical formula and sample problems (with answers) with discretion. Features include global surveys, boxes to introduce students to the frontiers of science, and original art and diagrams